Frequency of Oropharyngeal Cancer Among Males - Khan, Asghar; Kabir, Sofia; Musa, Nighat (Journal of Gandhara Medical and Dental Science, 2018)
OBJECTIVE: Background: Worldwide oropharyngeal cancers are one of ten most common cancers. A multitude of factors are responsible for the development of oropharyngeal cancers. Some factors are non- modifiable like age, sex, genetics and many are modifiable risk factors like tobacco use, chewing betel nuts, eating paan, alcohol and UV light exposure etc. The main purpose of this study was to analyze frequency and different risk factors associated with oropharyngeal cancers among males visiting tertiary care hospitals of Peshawar. METHODOLOGY: A cross-sectional study was conducted on 100 male patients having different cancers visiting tertiary care hospitals of Peshawar. Study duration was 5 months from January to May 2015. Non-probability convenient sampling technique was used. Semi-structured questionnaire, Patient’s record were used as data collecting tools. Different risk factors were assessed and analyzed. RESULTS: Frequency of oropharyngeal cancers was found to be 19%. Common risk factors among these patients were prolong Ultra violet light exposure (4-8 hrs) 74%, 42% were smokers, 42% had history of oral thrush, 37% patients were in a habit of taking snuff regularly, 36% history of leukoplakia and 16% had smoked meat diet history. CONCLUSION: Prolong exposure to ultra violet radiations, smoking, snuff and human papiloma virus increases risk of patients for oropharyngeal cancers.